143k views
3 votes
See the screen shot below. Can anyone help me with this one

See the screen shot below. Can anyone help me with this one-example-1
User Tom Auger
by
5.3k points

2 Answers

3 votes

Answer:

Top one

Explanation:

turn b² into a fraction of h, so b2h/h

User Zpete
by
5.9k points
0 votes

For this case we have the following equation to find
b_ {1}


b_ {1} = \frac {2A} {h} -b_ {2}\\\\

If we want to find an equivalent equation, we do the following:


(2A)/(h)-b_(2)=(2A*1-b_(2)*h)/(h)=(2A-b_(2)h)/(h)\\\\

So, we have to:


b_ {1} = \frac {2A} {h} -b_ {2} = \frac {2A-b_ {2} h} {h}\\

Answer:

Option A

User David Beckwith
by
5.5k points